Social programs and financial inclusion: instruments of biopolitics in Peru, 2000–2024 - Morales Rocha, Jose Luis; Lauracio Ticona, Teófilo; Coyla Zela, Mario Aurelio; Ramos Rojas, Jarol Teófilo; Serruto Medina, Genciana; Vargas Torres, Nakaday Irazema; Lauracio Lope, Claudia Jessica (Frontiers in Political Science, 2025)
Biopolitics refers to the set of public policies and state actions aimed at regulating the vital functions of individuals and societies, including areas such as public health, democracy, citizen security, and quality of life. This article analyzes the biopolitical instrumentalization of fiscal policies and financial governmentality in Peru between 2000 and 2024. The research is based on the hypothesis that Peruvian governments have used these tools to promote equitable human development. Using correlation and regression tests, we examined social programs, financial inclusion indicators, and variations in the Gross Domestic Product (GDP) in relation to the Human Development Index and other socioeconomic variables. The main conclusion indicates that the impact of social programs and financial inclusion is limited at the regional level. Only the percentage of financial debtors and the Juntos Program show a significant effect on human development indicators such as malnutrition, monetary poverty, and academic performance. Despite being considered essential for sustainable development, social programs and financial inclusion in Peru during this period were instrumentalized for biopolitical purposes, prioritizing capitalist reproduction and the exploitation of resources from less developed regions. Although economic growth was achieved, there was no corresponding promotion of equity, social inclusion, or comprehensive human development. Notably, the poverty rate in Peru increased to 29.0% in 2023, approaching the levels recorded during the 2020 pandemic (30.1%), according to the Peruvian Institute of Economics, and continued to rise in 2024, reflecting the inadequacy of the implemented policies.